The Potential of Using Liquid Hot Water Pretreated Rice Straw to Produce Environment Friendly Particleboard - Peng Luo; Yan He; Tao Wang (BioResources, 2024)
The high extractives content in rice straw severely hinders surface adhesion, resulting in poor strength and dimensional stability of rice straw particleboard bonded with castor oil-based polyurethane (CPUR) resin. In this study, rice straw was pretreated with liquid hot water (LHW) at 150 °C for 20 min to reduce its extractives content for particleboard production with CPUR resin. The effects of LHW pretreatment on the chemical composition of the rice straws was evaluated.  In addition, effects of CPUR resin dosage and density on mechanical properties and dimensional stability of the rice straw particleboards were investigated. The results indicated that LHW pretreatment significantly reduced the extractives and hemicellulose contents of the rice straw. The LHW pretreatment significantly improved the mechanical properties and dimensional stability of the rice straw particleboards. The overall performances of the rice straw particleboards were enhanced as the CPUR dosage increased. Increase of density led to upgraded mechanical properties but lowered dimensional stability of the rice straw particleboards.